2009
DOI: 10.1080/00016480701724888
|View full text |Cite
|
Sign up to set email alerts
|

Amplitude and area ratios of summating potential/action potential (SP/AP) in Meniere's disease

Abstract: With regard to SP/AP amplitude ratio, 57.1% in definite cases of MD (group 1), 39.6% in probable cases of MD (group 2), and 50.0% in the cases who had transformed from probable MD to definite MD (group 3) showed abnormally high values, respectively. Abnormally high values were observed in 43.9%, 27.7%, and 30.0% in SP/AP area ratio in groups 1, 2, and 3, respectively, indicating that abnormal values were observed more frequently in the amplitude ratio than in the area ratio in all three groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 16 publications
2
24
0
1
Order By: Relevance
“…Especially MD had a high incidence of 57.6%, almost the same as reported by Baba et al [9] . However, the value was relatively low compared with the previously reported high incidence of 71-76.1% [5][6][7] .…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Especially MD had a high incidence of 57.6%, almost the same as reported by Baba et al [9] . However, the value was relatively low compared with the previously reported high incidence of 71-76.1% [5][6][7] .…”
Section: Discussionsupporting
confidence: 76%
“…As to the recording technique, the transtympanic technique was introduced to yield a good output and signalto-noise ratio in addition to the less invasive extratympanic and tympanic techniques. However, although there are some conflicting arguments, the incidence of an enhanced SP is no more than 55-75% even in confirmed cases of MD [5][6][7][8][9] . This means that endolymphatic hydrops does not always result in enhancement of the SP.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to SP/AP AUC, they found 43.9%, 27.7%, and 30% respectively, concluding that the analysis of SP/AP AUC with transtympanic electrocochleography does not necessarily increase the sensitivity in the diagnosis of endolymphatic hydrops compared with SP/AP amplitude. 25 Ikino et al used transtympanic electrocochleography to examine 21 patients with definite Ménière's disease and 19 normal hearing patients with other cochleovestibular disorders. They compared SP/AP, AP latency difference, and area under curve of SP/AP ratio and calculated the diagnostic sensitivity of these parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Lamounier et al also found in the systematic review that the analysis of the SP/AP ratio curve of the transtympanic electrocochleography did not necessarily increase sensitivity in the diagnosis of hydrops when compared with the SP/AP amplitude [14,[16][17][18].…”
Section: Electrocochleography (Ecochg)mentioning
confidence: 99%
“…In most studies selected, the transtympanic electrode is the most widely used. EcochG in MD presents a variable sensitivity, as in cases of hearing loss due to disease progression, patients may experience a reduction in the amplitude of AP due to loss of auditory nerve fibers [14][15][16][17].…”
Section: Electrocochleography (Ecochg)mentioning
confidence: 99%